Fausto E. Barbo, João Luiz Gasparini, Antonio P. Almeida, Hussam Zaher, Felipe G. Grazziotin,Rodrigo B. Gusmão, José Mário G. Ferrarini & Ricardo J. Sawaya (2016)Another new and threatened species of lancehead genus Bothrops (Serpentes, Viperidae) from Ilha dos Franceses, Southeastern Brazil. Zootaxa 4097 (4): 511–529. - Barbo, Fausto E.; Gasparini, João Luiz; Almeida, Antonio P.; Zaher, Hussam; Grazziotin, Felipe G.; Gusmão, Rodrigo B.; Ferrarini, José Mário G.; Sawaya, Ricardo J. (Zootaxa, 2016)
N/A